HARMONIZATION OF TRADITION AND ISLAM IN BANJAR DIAMOND CRAFTS: ANALYSIS OF ISLAMIC EDUCATIONAL PHILOSOPHY AND ITS RELEVANCE FOR CHARACTER EDUCATION - Adawiah, Rabiatul; Sakdiah, Halimatus; Jainie, Inawati Mohammad; Hafidzi, Anwar (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The customary and Islamic traditions that color Banjar diamond craft activities contain noble and important values in character formation in Islamic education. Objective: This research aims to examine Banjar diamond crafts, both in the activities of diamond panning and polishing, by exploring local and Islamic customs and the character values contained there in and analyzing them from the perspective of Islamic educational philosophy. Method: This research uses a qualitative method with an ethnographic approach. Data collection was conducted through observation, interviews, and triangulation with Banjar diamond miners and polishers. Result: The research results show that there is three dimensions of harmonization of custom and Islam in Banjar diamond crafts, namely the dimensions of religious practice, work ethics, and local wisdom. The three dimensions of harmonization of custom and Islam are relevant to character education as follows. First, religious practice forms the character of piety, obedience to worship, spiritual awareness that efforts must be intended as worship, responsibility, sincerity and gratitude as important elements in the dimension of religious character. Second, work ethics forms the character of hard work, resilience, honesty, and responsibility, as well as diligence, perseverance, tenacity and patience as the development of persistent and integrity character. Third, local wisdom forms the character of respect for tradition, cooperation, tolerance, civilization, and a strong cultural identity. Conclusion: The overall practice of harmonization of custom and Islam in diamond crafts from the perspective of Islamic Educational Philosophy, both perennially and essentially, strongly shapes the character of Banjar society. Harmonization between custom and Islam in Banjar diamond crafts is a manifestation of local wisdom as well as a primary source in character education. Thus, this study enriches the literature on character education, cultural education, and also the philosophy of Islamic education.